In-plane electrical conductivity of PEDOT:PSS/Halloysite composite thin films - Isidro Cruz-Cruz; Roberto I. Servín-Quintero; Luis Marcelo Lozano; Alan O. Sustaita (Heliyon)
PEDOT:PSS has found numerous applications in the field of advanced materials, especially in the development of organic electronics. Embedding nanoparticles into the polymer matrix has emerged as an effective strategy to modify the properties of PEDOT:PSS and develop advanced functional composites. Over the past decade, Halloysite nanotubes (HNT) have garnered significant interest and utility as nanofillers and/or templates due to their unique physical-chemical properties, small size, relatively low cost, and large availability. Interestingly, pairing PEDOT:PSS with non-conductive HNT has been demonstrated to enhance the charge transport properties of the composite film. Our discoveries show how the HNT can act as scaffolding for PEDOT:PSS by improving the local ordering of PEDOT chains and enabling the formation of conductive pathways. Consequently, the mechanism responsible for the observed changes in conductivity and the correlation between PEDOT:PSS and insulating nanofillers (HNT) could be different to that previously proposed. Hence, in this work it was observed that PEDOT:PSS/HNT composite films exhibited a non-linear conductivity dependence as a function of the HNT loading. From thermogravimetric analysis, infrared and UV-Vis-NIR spectroscopies, as well as impedance spectroscopy, a more complex interaction between the polymer chains and the nanotubes is revealed. Our study includes the modification of the interaction between the PEDOT chains and the nanofillers by using the secondary doping effect and functionalization of the nanotubes, which confirms our findings. These results represent a significant progress toward a deeper understanding of the emergence of a conductive polymer network on the nanofiller surface, leading to improvements in the electrical conductivity in the composite material.